Carbon-free sodium ion battery negative electrode material, preparation method thereof and sodium ion battery

By mixing different types of transition metal oxygen/sulfides with ball mills or baking them with precursors, layered negative electrode materials containing rich heterointerfaces are prepared, which solves the electrochemical reaction kinetics and cycles of the negative electrode materials of sodium ion battery. Stability issues achieve high specific capacity and rate performance.

CN119480957AInactive Publication Date: 2025-02-18AMPREUS WUXI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411499948.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrochemical reaction kinetics of existing sodium ion battery anode materials during sodium storage are not ideal, and the cycle stability is poor, which cannot meet the requirements of rapid migration and high-rate performance of sodium ions.

Method used

Laminated negative electrode materials containing rich heterointerfaces are prepared by mixing different types of transition metal oxygen/sulfide ball milling, or ball milling and calculating the transition metal oxygen/sulfide precursor and the transition metal oxygen/sulfide. This method enhances the electron transport capability and structural stability of the material by forming multiple heterogeneous interfaces.

Benefits of technology

The cyclic specific capacity and rate performance of the negative electrode material of sodium ion battery is improved, the stability of the material during the charging and discharging process is enhanced, and the rapid migration of sodium ions and high power density are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480957A_ABST
    Figure CN119480957A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-free sodium ion battery negative electrode material, a preparation method thereof and a sodium ion battery, and belongs to the technical field of battery materials. The negative electrode material disclosed by the invention is a compound of nano transition metal oxide / sulfide at least comprising two thin layers; or a complex comprising a thin layer of nanotransition metal oxides / sulfides and particulate nanotransition metal oxides / sulfides; the thickness of the nano transition metal oxide / sulfide of the thin layer is 2-50nm; and the particle size of the granular nano transition metal oxide / sulfide is less than or equal to 80 nm. According to the invention, the transition metal oxide / sulfide is mixed and ball-milled, or the precursor of the transition metal oxide / sulfide and the transition metal oxide / sulfide are ball-milled and roasted to obtain the layered negative electrode material containing rich heterogeneous interfaces, and the prepared negative electrode material enhances the stability of the heterogeneous interfaces of the material in the charge-discharge process, improves the specific capacity after circulation, and improves the performance of the material. And when the material is used as a sodium ion battery negative electrode material, the material has excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a carbon-free sodium ion battery negative electrode material, a preparation method thereof, and a sodium ion battery. Background Art

[0002] The global new energy vehicle and energy storage industries are growing rapidly and continuously, and lithium resources, as core raw materials, have become an important factor restricting the development of the industry due to supply and demand mismatches and economic issues. Sodium resources are abundant and evenly distributed, and compared with lithium batteries, they have advantages in low temperature, rate performance and economy. Therefore, sodium batteries will become an effective supplement to lithium-ion batteries in the fields of energy storage, commercial vehicles and some passenger cars. The working principle of sodium batteries is similar to that of lithium-ion batteries, but because the radius of sodium ions is larger than that of lithium ions, some negative electrode materials used in lithium-ion batteries are not suitable for sodium-ion batteries. For example, in lithium-ion batteries, graphite can play a role of about 372mAh g -1 The theoretical specific capacity of sodium ion batteries is 25 mA hg. -1 specific capacity. Layered metal oxysulfides are a class of very promising energy storage materials, which are composed of a single-layer structure stacked by weak van der Waals forces, so their interlayer spacing is large and there are a large number of active reaction sites between the layers. In addition, transition metal elements, such as Mo, W, V and other metals, have rich oxidation states, so their corresponding layered transition metal oxysulfides MoO3 / WO3 / V2O5 and MoS2 / WS2 / VS2 have high theoretical specific capacity. However, bulk transition metal oxysulfides have poor conductivity and the interlayer spacing cannot meet the rapid migration of sodium ions, so the electrochemical reaction kinetics of this type of material in the sodium storage process is not ideal. In addition, the pure layered transition metal oxysulfide has a significant volume effect during the charge and discharge process, so its cycle stability is not ideal. There are currently two common methods to solve the above problems. The first is to reduce the size of the layered transition metal oxysulfide to reduce Na +diffusion path and increase the contact area between the electrode and the electrolyte. Second, the layered transition metal oxysulfide is compounded with carbon or other transition metal oxysulfides into a heterostructure to increase the electronic conductivity and reaction kinetics of the material. For example, the research group of Professor Cui Deliang of Shandong University prepared an alternating intercalation structure of layered MoS2 and carbon to improve the conductivity of pure MoS2 and increase its interlayer spacing, reduce the ion diffusion barrier, and improve the sodium storage capacity and structural stability of the composite material (JWSun, DLCui, et al., Hierarchical MoS2 / mC@aC@Ti3C2 nanohybrids as superior electrodes for enhanced sodium storage and hydrogen evolution reaction, Chem.Eng.J.2021,421:129680.). In addition, heterogeneous materials of different metal oxysulfides have also attracted widespread attention. For example, CN 114899379A discloses a method of electrospinning and high-temperature calcination to prepare a composite of SnSe / SnTe nanoparticles and porous carbon nanofibers, which exhibits excellent sodium ion storage performance. Professor Song Bo's research group at Harbin Institute of Technology used freeze-drying to prepare a MoO2 / MoS2 composite for sodium ion battery negative electrode materials using foamed carbon as a carrier. MoO2 / MoS2 constructs the intrinsic electric field of the composite material, which is beneficial to increase the kinetics and structural stability of the electrochemical reaction of the material. Foamed carbon acts as a conductive framework to increase the mobility of electrons and ions inside the material (XFLi, B. Song, et al., Synergistically Designed Dual Interfaces to Enhance the Electrochemical Performance of MoO2 / MoS2 in Na-and Li-Ion Batteries, Small, 2023, 19, 2206940). In this type of material, crystals with different band gaps at the heterogeneous interface couple and form a special electric field. However, in this type of material, relatively few and discontinuous heterogeneous interfaces are generally constructed, which cannot guarantee the long-term cycle stability and electrochemical reaction kinetics of the material. Therefore, it is still necessary to compound with carbon to increase the conductivity and structural stability of the material, or to minimize the size of the material to the greatest extent. In addition, this type of material generally contains only transition metal oxides or transition metal sulfides, and the combination form of the composite is subject to certain restrictions. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a carbon-free sodium ion battery negative electrode material, a preparation method thereof, and a sodium ion battery. The present invention obtains a negative electrode material based on a thin layer of transition metal oxysulfide with rich heterogeneous interfaces by mixing and ball-milling different types of transition metal oxides / sulfides, or ball-milling a transition metal oxide / sulfide precursor with a transition metal oxide sulfide, and then calcining. The rich heterogeneous interfaces in the prepared negative electrode material enhance the stability of the material during the charge and discharge process, improve the specific capacity after the cycle, and at the same time, improve the electron transmission ability of the material, so that the material has excellent specific capacity and rate performance when used as a negative electrode material for a sodium ion battery.

[0004] The technical solution of the present invention is as follows:

[0005] The first aspect of the present invention protects a carbon-free negative electrode material, wherein the negative electrode material is a composite of at least two thin layers of nano transition metal oxygen / sulfide; or, the negative electrode material is a composite of a thin layer of nano transition metal oxygen / sulfide and granular nano transition metal oxygen / sulfide; the thickness of the thin layer of nano transition metal oxygen / sulfide is 2-50nm; the particle size of the granular nano transition metal oxygen / sulfide is ≤80nm.

[0006] Preferably, the structural formula of the nano transition metal oxide / sulfide is A x B y ; wherein, A is selected from at least one of Mo, W, V, Ti, Co, Ni, and Fe; B is selected from at least one of O and S; 0<x≤3; 0<y≤3.

[0007] Preferably, the nano transition metal oxide / sulfide includes at least one of MoO3, MoO2, WO3, WO2, VO2, TiO2, CoO2, NiO2, MoS2, WS2, VS2, MnS2, TiS2, FeS2, CoS2, and NiS2.

[0008] The second aspect of the present invention protects a method for preparing the carbon-free negative electrode material according to the first aspect, the preparation method comprising the following steps:

[0009] At least two transition metal oxide / sulfide raw materials are mixed to obtain a mixed material I, and then ball milled; or, a transition metal oxide / sulfide raw material is mixed with a transition metal oxide / sulfide precursor to obtain a mixed material II, and then ball milled and calcined.

[0010] Preferably, the transition metal oxygen / sulfide raw material includes at least one of MoO3, MoO2, WO3, WO2, VO2, TiO2, CoO2, NiO2, MoS2, WS2, VS2, MnS2, TiS2, FeS2, CoS2, and NiS2; and the average particle size of the transition metal oxygen / sulfide raw material is 1-900 μm.

[0011] Preferably, the transition metal oxide / sulfide precursor comprises a cation and an anion, wherein the cation is selected from NH4 + 、Mo 6+ 、Na + , W 6+ 、V 5+ 、Ti 4+ At least one of; the anion is selected from O 2- , S 2- At least one of the following: the average particle size of the transition metal oxide / sulfide precursor is 500nm-3μm.

[0012] Preferably, the transition metal oxide / sulfide precursor includes at least one of ammonium molybdate, ammonium thiomolybdate and ammonium thiotungstate.

[0013] Preferably, in the mixed material I, the molar ratio of any two transition metal oxides / sulfides is m1:1, wherein 1≤m1≤8; in the mixed material II, the molar ratio of the transition metal oxide / sulfide precursor to the transition metal oxide / sulfide raw material is m2:1, wherein 1≤m2≤8.

[0014] Preferably, the mass ratio of the grinding balls of the ball mill to the mixed material I is n1:1, wherein 3≤n1≤30; the mass ratio of the grinding balls of the ball mill to the mixed material II is n2:1, wherein 3≤n2≤30; the ball milling time is 5-15h, and the ball milling speed is 200-800r / min; the calcination is carried out under an inert atmosphere, and the inert atmosphere is pure N2 or Ar; the calcination temperature is 400-800℃, and the time is 2-10h.

[0015] The third aspect of the present invention protects a sodium ion battery, comprising a negative electrode material, wherein the negative electrode material comprises the negative electrode material prepared by the preparation method described in the second aspect or the negative electrode material described in the first aspect.

[0016] The beneficial technical effects of the present invention are:

[0017] The present invention obtains a layered negative electrode material containing rich heterogeneous interfaces by ball-milling a transition metal oxide / sulfide mixture, or ball-milling a transition metal oxide / sulfide precursor with a transition metal oxide / sulfide and then calcining. The multiple heterogeneous interfaces can realize the coupling of crystal materials with different band gaps and the modulation of the electric field structure. At the same time, a large number of chemical bonds are likely to be formed between thin layers of transition metal oxide / sulfide, thereby enhancing the stability of the material heterogeneous interface during the charge and discharge process, improving the specific capacity after the cycle, and at the same time, improving the electron transmission ability of the material, so that the material has excellent rate performance when used as a negative electrode material for a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a transmission electron micrograph of the product obtained after ball milling and calcination of ammonium thiomolybdate and MoO3 in Example 4 of the present invention.

[0019] Figure 2 This is the SEM image of the MoO3 raw material used in the present invention.

[0020] Figure 3 This is a SEM image of the product obtained after ball milling of single MoO3 in Comparative Example 1 of the present invention.

[0021] Figure 4 This is the TEM image of the product obtained after ball milling of single MoO3 in Comparative Example 1 of the present invention.

[0022] Figure 5 This is a transmission electron micrograph of the product obtained by ball milling and calcining single ammonium thiomolybdate in comparative example 2 of the present invention.

[0023] Figure 6 This is a high-resolution transmission electron micrograph of the product obtained after co-sphering, grinding and calcining of single ammonium thiomolybdate and MoO3 obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0025] In view of the problems of existing negative electrode materials for sodium ion batteries, the present invention provides a carbon-free negative electrode material for sodium ion batteries. Without introducing carbon, by thin-layering the transition metal oxide / sulfide, in particular, by achieving alternating stacking of different transition metal oxide / sulfide materials, the problem of re-aggregation of a single transition metal oxide / sulfide after being stripped is solved. At the same time, the obtained hybrid composite material has a rich and stable heterogeneous interface. The heterogeneous interface layer realizes the coupling of crystals with different band gaps, enhances the modulatability of the electric field structure, and enhances the kinetic process of the electrochemical reaction through the electric field construction of the heterogeneous interface. Further, through the selection of materials, abundant chemical bonds will be formed at the heterogeneous interface, which greatly enhances the structural stability at the material interface, thereby making it more likely to obtain a sodium ion battery negative electrode material with high power density and good cycle stability.

[0026] The first aspect of the present invention provides a carbon-free sodium ion battery negative electrode material, wherein the negative electrode material is a composite of at least two thin layers of nano transition metal oxygen / sulfide; or, the negative electrode material is a composite of a thin layer of nano transition metal oxygen / sulfide and a granular nano transition metal oxygen / sulfide; the thickness of the thin layer of nano transition metal oxygen / sulfide is 2-50nm, preferably 2-20nm. The particle size of the granular nano transition metal oxygen / sulfide is ≤80nm.

[0027] It is understandable that the nano transition metal oxide / sulfide refers to nano transition metal oxide or nano transition metal sulfide.

[0028] In some embodiments, the negative electrode material is a composite of at least one thin layer of nano transition metal oxide and at least one thin layer of nano transition metal sulfide alternately stacked, wherein the alternate stacking includes but is not limited to completely overlapping stacking or cross-irregular stacking between thin layers.

[0029] In some embodiments, the negative electrode material is a composite comprising alternately stacked thin layers of nano transition metal oxide and at least one thin layer of nano transition metal sulfide.

[0030] In some embodiments, the negative electrode material is a composite material comprising a thin layer of nano transition metal oxide / sulfide and a granular nano transition metal oxide / sulfide.

[0031] In some embodiments, the composite includes a thin layer of nano transition metal oxide and a granular nano transition metal sulfide, or includes a thin layer of nano transition metal sulfide and a granular nano transition metal oxide, which can provide more SO bonds, improve the bonding strength of the heterogeneous interface, and form a stable internal electric field at the heterogeneous interface, which is beneficial to increase the transfer rate of internal charges in the material, and ensure the stability of the negative electrode material layers without introducing carbon or MOF structure, and ensure the rapid transmission of sodium ions and electrons, thereby improving the specific capacity after cycling.

[0032] In some embodiments, the negative electrode material is a composite comprising a thin layer of nano transition metal oxide / sulfide and granular nano transition metal oxide / sulfide. The present invention does not limit the relative distribution of the thin layer of nano transition metal oxide / sulfide and the granular nano transition metal oxide / sulfide in the composite. Preferably, the granular nano transition metal oxide / sulfide is distributed between the thin layer of nano transition metal oxide / sulfide and / or the granular nano transition metal oxide / sulfide and the thin layer of nano transition metal oxide / sulfide are distributed alternately or staggered.

[0033] In some embodiments, the nano transition metal oxide / sulfide has the general structural formula A x B y ; wherein, A is selected from at least one of Mo, W, V, Ti, Co, Ni, and Fe; B is selected from at least one of O and S; 0<x≤3; 0<y≤3, x includes but is not limited to 1, 2, and 3; y includes but is not limited to 1, 2, and 3.

[0034] In some embodiments, the nano transition metal oxide / sulfide includes at least one of MoO3, MoO2, WO3, WO2, VO2, TiO2, CoO2, NiO2, MoS2, WS2, VS2, MnS2, TiS2, FeS2, CoS2, and NiS2.

[0035] The second aspect of the present invention protects a method for preparing the carbon-free negative electrode material described in the first aspect, and the preparation method comprises the following steps: mixing at least two transition metal oxide / sulfide raw materials to obtain a mixed material I, and ball milling; or, mixing the transition metal oxide / sulfide raw material with a transition metal oxide / sulfide precursor to obtain a mixed material II, ball milling, and calcining.

[0036] In some embodiments, the preparation method of the carbon-free negative electrode material is: mixing at least two transition metal oxide / sulfide raw materials to obtain a mixed material I, and ball milling to obtain, preferably, the mixing is to mix two different transition metal oxides / sulfides. More preferably, the mixing is to mix two transition metal oxides / sulfides with different anions. For example, at least one transition metal oxide raw material is mixed with at least one transition metal sulfide raw material to obtain a mixed material I.

[0037] It can be understood that the bonding of different elements between layers enhances the stability of the material's heterogeneous interface during the charge and discharge process. At the same time, it also improves the electron transmission capacity, making the material have excellent rate performance when used as a negative electrode material for sodium ion batteries.

[0038] In some embodiments, the transition metal oxygen / sulfide raw material includes at least one of MoO3, MoO2, WO3, WO2, VO2, TiO2, CoO2, NiO2, MoS2, WS2, VS2, MnS2, TiS2, FeS2, CoS2, and NiS2.

[0039] It is understood that the transition metal oxygen / sulfide raw material of the present invention is preferably a mixture of MoO3 and MoS2, or a mixture of WO3 and MoS2. More preferably, the mixture is a mixture of MoO3 and MoS2. The bond energy of the Mo-O bond is relatively small, and the SO bond is more easily formed at the interface of the hybrid structure.

[0040] In some embodiments, the average particle size of the transition metal oxide / sulfide raw material is 1-900 μm. In some embodiments, in the mixed material I, the molar ratio of any two transition metal oxides / sulfides is m1:1; wherein 1≤m1≤8.

[0041] It is understandable that, during the ball milling process of the present invention, a transition metal oxygen / sulfide bulk raw material and another transition metal oxygen / sulfide bulk material are used in a ball milling jar through ball milling impact force and tangential force, and the transition metal oxygen / sulfide will be peeled off from each other to form a thin layer of two-dimensional nano transition metal oxygen / sulfide orderly stacked composite hybrid structure. The staggered stacked hybrid structure has a rich heterogeneous interface, which improves the ability of the material to transfer charge and increases the reaction kinetics of the sodium storage process. At the same time, the structure can alleviate the volume effect caused by the electrochemical reaction during the sodium storage process, improve the structural stability of the material, and thus increase the cycle stability of the battery. This type of material avoids the use of carbon, and the active substance in the electrode material has a different sodium storage mechanism from carbon, so the sodium storage performance is higher than that of carbon. And compared with carbon-containing negative electrode materials, the specific surface area of ​​the obtained hybrid structure is relatively small, so it has the potential to become an electrode material with high volume energy density.

[0042] It can be understood that during the ball milling process, the transition metal oxide / sulfide raw materials are exfoliated into thin nanosheets. In the heterogeneous composite material, the two transition metal oxide / sulfide nanosheets act as dispersants and inhibitors for each other, and are tightly intertwined and stacked with each other to form a large number of heterogeneous interfaces.

[0043] In some embodiments, the negative electrode material is prepared by mixing a transition metal oxide / sulfide raw material with a transition metal oxide / sulfide precursor to obtain a mixed material II, ball milling, and calcining the mixed material.

[0044] In some embodiments, the composition of the product obtained after calcining the transition metal oxide / sulfide precursor is the same as or different from the composition of the transition metal oxide / sulfide raw material mixed and ball-milled with the precursor.

[0045] In some embodiments, the negative electrode material is prepared by mixing a transition metal oxide raw material with another transition metal sulfide precursor to obtain a mixed material II, ball milling, and then calcining the mixed material.

[0046] In some embodiments, the negative electrode material is prepared by mixing a transition metal sulfide raw material with another transition metal oxide precursor to obtain a mixed material II, ball milling, and then calcining the mixed material.

[0047] It can be understood that in some embodiments of the present invention, by introducing a transition metal oxide / sulfide precursor and co-ball milling with a transition metal oxide / sulfide raw material, the precursor can be used as an ionic crystal with high hardness and irregular crystal structure. The characteristics of the structure can better transmit and increase the impact force and tangential force of ball milling, so that the transition metal oxide / sulfide raw material is fully stripped, and the precursor itself is also fragmented. Through further calcination, it is converted into the corresponding metal oxide / sulfide material, thereby realizing the orderly composite of layered transition metal oxide / sulfide and small-sized transition metal oxide / sulfide. Compared with the mixed material containing only different transition metal oxide / sulfide raw materials, one transition metal oxide / sulfide in the target product is introduced in the form of a precursor, and the related anions in the precursor have relatively more free lone pairs of electrons, and the interaction between it and the cations in another transition metal oxide / sulfide is strengthened, which weakens the interlayer interaction of the transition metal oxide / sulfide to a certain extent, so as to be more conducive to the realization of stripping, improve the stripping efficiency and reduce the number of layers of the stripping product. In addition, the precursor is more likely to form a new stable chemical bond with another transition metal oxide / sulfide at the interface during the conversion reaction during high-temperature calcination. The electrode material obtained in this way will have improved active reaction sites and charge transfer capabilities when storing sodium.

[0048] In some embodiments, the transition metal oxide / sulfide precursor comprises a cation and an anion, wherein the cation is selected from NH4 +、Mo 6+ 、Na + , W 6+ 、V 5+ 、Ti 4+ At least one of; the anion is selected from O 2- , S 2- At least one of the following: the average particle size of the transition metal oxide / sulfide precursor is 500nm-3μm.

[0049] In some embodiments, the transition metal oxide / sulfide precursor includes at least one of ammonium molybdate, ammonium thiomolybdate, and ammonium thiotungstate.

[0050] In the mixed material II, the molar ratio of the transition metal oxide / sulfide precursor to the transition metal oxide / sulfide raw material is m2:1, wherein 1≤m2≤8.

[0051] It is understood that the ball milling equipment of the present invention includes a grinding jar and a planetary grinder. The materials of the grinding balls used include stainless steel, corundum, zirconium oxide, agate, preferably zirconium oxide. The diameter of the grinding balls is 1 mm-20 mm.

[0052] In some embodiments, the mass ratio of the grinding balls of the ball mill to the mixed material I is n1:1, wherein 3≤n1≤30.

[0053] In some embodiments, the mass ratio of the grinding balls of the ball mill to the mixed material II is n2:1, wherein 3≤n2≤30.

[0054] In some embodiments, the ball milling time is 5-15 hours, including but not limited to 5 hours, 8 hours, 10 hours, 12 hours, 14 hours, and 15 hours. The ball milling speed is 200-800 r / min, including but not limited to 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, and 800 r / min.

[0055] In some embodiments, the calcination is carried out under an inert atmosphere, which is pure N2 or Ar; the calcination temperature is 400-800°C, including but not limited to 400°C, 500°C, 600°C, 700°C, 800°C, and the calcination time is 2-10h, including but not limited to 2h, 4h, 6h, 8h, 10h.

[0056] It can be understood that the present invention further improves the peeling and fragmentation effects by optimizing the ball milling parameters, making the composite more uniformly hybridized. The thin layer structure has fewer layers, and the radial size of the plane is more suitable for compounding with another nanomaterial to obtain more heterogeneous interfaces, thereby optimizing the performance of the negative electrode material.

[0057] It can be understood that the present invention obtains a layered composite material with rich and stable heterogeneous interfaces by co-ball milling a transition metal oxide / sulfide precursor with another transition metal oxide / sulfide raw material, and then post-treating it by calcination. Compared with the electrode material directly obtained by using two different layered transition metal oxides / sulfides, the method has the advantages of uniform and sufficient exfoliation and composite, rich heterogeneous interfaces, and easy formation of stable chemical bonds at the interface.

[0058] A third aspect of the present invention provides a sodium ion battery, comprising a negative electrode material, wherein the negative electrode material comprises the negative electrode material prepared by the preparation method described in the second aspect or the negative electrode material described in the first aspect.

[0059] The present invention will be further described below by way of examples and the like.

[0060] Example 1

[0061] A carbon-free negative electrode material, the preparation method of which is as follows:

[0062] At a molar ratio of 3:1, weigh 1.25g MoO3 and 0.717g WS2 and add them to the ball mill. Then add grinding beads in a ratio of 30:1 between the total mass of the ball mill and the total mass of the raw materials. The diameters of the ball mills are 5mm and 3mm, respectively, and the ratio of large beads to small beads is 3:1. Then add isopropanol to the ball mill to immerse the ball mills and raw materials, and use a planetary ball mill for ball milling at a speed of 450r·min -1 After ball milling for 14 hours, a MoO3-WS2 composite was obtained. In the MoO3-WS2 composite, MoO3 and WS2 formed a thin layer stacking composite structure, and the thickness of the thin layer was 2-50nm.

[0063] Sodium ion battery, the preparation method thereof is as follows:

[0064] The MoO3 / WS2 composite obtained above was used as an electrode material and mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1. After being stirred evenly in a methyldipyrrolidone (NMP) solution, it was coated on a copper foil and dried in a vacuum to form an electrode sheet. A CR2032 button cell was assembled using a sodium sheet as an electrode, Celgard 2502 membrane as a diaphragm, sodium hexafluorophosphate NaPF6 + propylene carbonate PC + fluoroethylene carbonate FEC as an electrolyte.

[0065] Example 2

[0066] A carbon-free negative electrode material, the preparation method of which is as follows:

[0067] At a molar ratio of 3:1, weigh 0.77g MoS2 and 0.23g MoO3 and add them to the ball mill; then add 30g grinding beads according to the ratio of the total mass of the ball milling beads to the total mass of the raw materials of 30:1. The diameters of the ball milling beads are 5mm and 3mm respectively, and the ratio of large beads to small beads is 3:1. Then add isopropanol to the ball milling jar to immerse the ball milling beads and raw materials, and use a planetary ball mill for ball milling at a speed of 450r·min -1 , ball milled for 14 h to obtain the MoS2-MoO3 composite.

[0068] The preparation method of the sodium ion battery is basically the same as that of Example 1, except that the negative electrode material used is replaced by the negative electrode material of this example.

[0069] Example 3

[0070] A carbon-free negative electrode material, the preparation method of which is as follows:

[0071] At a molar ratio of 3:1, weigh 1.25g (NH4)2MoS4 and 0.23g MoO3 respectively and add them to a 50mL ball mill. In addition, according to the ratio of the total mass of the ball milling beads to the total mass of the mixed material of 30:1, weigh 44.4g of ball milling beads and add them to the ball mill. The diameters of the ball milling beads are 5mm and 3mm respectively, and the ratio of large beads to small beads is 3:1. Then add isopropanol to the ball milling jar to immerse the ball milling beads and samples, and use a planetary ball mill for ball milling at a speed of 450r·min -1 The (NH4)2WS2-MoO3 composite was obtained by ball milling for 14 hours. After drying, it was calcined in a N2 atmosphere at 400°C for 5 hours to obtain a MoS2-MoO2 composite. The composite is a material with a hybrid structure in which thin-layer MoS2 and nano-MoO2 are uniformly compounded.

[0072] The sodium ion battery is prepared by mixing the obtained MoS2-MoO2 composite as an electrode material with a conductive agent, acetylene black, and a binder, polyvinylidene fluoride (PVDF), in a mass ratio of 7:2:1, stirring evenly in a methyldipyrrolidone (NMP) solution, coating the mixture on a copper foil, and drying the mixture under vacuum to form an electrode sheet. A CR2032 button cell is assembled using a sodium sheet as an electrode, a Celgard 2502 membrane as a diaphragm, sodium hexafluorophosphate NaPF6 + propylene carbonate PC + fluoroethylene carbonate FEC as an electrolyte.

[0073] Example 4

[0074] A carbon-free negative electrode material, the preparation method of which is as follows:

[0075] According to the molar ratio of 5:1, 1.25g (NH4)2MoS4 and 0.14g MoO3 are weighed and added to the ball mill; in addition, 41.7g grinding beads are added according to the ratio of the total mass of the ball milling beads to the total mass of the drug of 30:1; the diameters of the ball milling beads are 5mm and 3mm respectively, and the ratio of large beads to small beads is 3:1. The rest of the preparation method is the same as that of Example 3 to obtain a MoS2-MoO2 composite. The composite is a material with a hybrid structure in which thin-layer MoS2 and nano-MoO2 are uniformly composited.

[0076] The preparation method of the sodium ion battery is the same as that of Example 3, except that the negative electrode material used is replaced by the negative electrode material of this example.

[0077] Example 5

[0078] A carbon-free negative electrode material, the preparation method of which is as follows:

[0079] At a molar ratio of 1:1, weigh 1.25g (NH4)2MoS4 and 0.69g MoO3 powder respectively and add them to a 50mL ball mill. In addition, according to the ratio of the total mass of the ball milling beads to the total mass of the drug of 30:1, weigh 50.1g of ball milling beads and add them to the ball mill. The diameters of the ball milling beads are 5mm and 2mm respectively, and the ratio of large beads to small beads is 3:1. Then add isopropanol to the ball milling jar to immerse the ball milling beads and samples, and use a planetary ball mill for ball milling at a speed of 450r·min -1 The (NH4)2MoS4 / MoO3 composite was obtained by ball milling for 14 hours. After drying, it was calcined in a N2 atmosphere at 400°C for 5 hours to obtain a MoS2-MoO2 composite. The composite is a material with a hybrid structure in which thin-layer MoS2 and nano-MoO2 are uniformly compounded.

[0080] The preparation method of the sodium ion battery is the same as that of Example 3, except that the negative electrode material used is replaced by the negative electrode material of this example.

[0081] Example 6

[0082] A carbon-free negative electrode material, whose preparation is basically the same as that of Example 3, except for the type of raw materials. In this comparative example, the precursors (NH4)2MoS4 and MoS2 are mixed in a molar ratio of 3:1 and ball-milled, and then calcined to obtain a layered MoS2 negative electrode material.

[0083] Example 7

[0084] A carbon-free negative electrode material, the preparation of which is basically the same as that of Example 2, except that the raw materials are MoO3 and WO3, that is, 1.11g WO3 and 0.23g MoO3 are weighed and added to a ball mill jar at a molar ratio of 3:1, and finally a MoO3-WO3 composite is obtained. In the MoO3-WO3 composite, MoO3 and WO3 form a thin layer stacking composite structure, and the thickness of the thin layer is 2-50nm.

[0085] The preparation method of the sodium ion battery is basically the same as that of Example 1, except that the negative electrode material used is replaced by the negative electrode material of this example.

[0086] Example 8

[0087] A carbon-free negative electrode material, whose preparation is basically the same as that of Example 3, except that the raw materials are (NH4)2MoS4 and MoS2, that is, at a molar ratio of 3:1, 1.25g (NH4)2MoS4 and 0.26g MoS2 are weighed separately and added into a 50mL ball mill jar, and then ball milled and calcined to finally obtain a layered MoS2 negative electrode material.

[0088] The preparation method of the sodium ion battery is basically the same as that of Example 1, except that the negative electrode material used is replaced by the negative electrode material of this example.

[0089] Comparative Example 1

[0090] A negative electrode material, the preparation of which is basically the same as that of Example 2, except that the raw material is a transition metal oxide, that is, only MoO3 is used, and the amount used is 1g.

[0091] The preparation method of the sodium ion battery is basically the same as that of Example 1, except that the negative electrode material used is replaced by the negative electrode material of this comparative example.

[0092] Comparative Example 2

[0093] A negative electrode material, whose preparation is basically the same as that of Example 3, except that only the precursor is used, and the ball milling and then calcination are performed, that is, only 1.48g of ammonium thiomolybdate is used for ball milling and then calcination.

[0094] The preparation method of the sodium ion battery is basically the same as that of Example 1, except that the negative electrode material used is replaced by the negative electrode material of this comparative example.

[0095] Test example:

[0096] (1) Characterization of negative electrode materials

[0097] The raw materials and the prepared negative electrode materials of the embodiments and comparative examples were characterized by transmission electron microscopy, scanning electron microscopy, and charge and discharge tests. The results are as follows: Figure 1-6 As shown. Among them, Figure 1This is a transmission electron micrograph of the product obtained after ball milling and calcination of ammonium thiomolybdate and MoO3 in Example 4.

[0098] Figure 2 This is the SEM image of MoO3 raw material. Figure 3 This is the SEM image of the product prepared in Comparative Example 1.

[0099] Figure 4 This is the TEM image of the product obtained in Comparative Example 1. Figure 5 This is a transmission electron microscope image of the product obtained after ball milling and calcination of single ammonium thiomolybdate in Comparative Example 2. Figure 6 This is a high-resolution transmission electron microscopy image of the product obtained in Example 4.

[0100] Depend on Figure 2-5 It can be seen that ball milling or ball milling followed by calcination of a single raw material cannot produce a composite material containing multiple heterogeneous interface layers.

[0101] Depend on Figure 1 and 6 It can be seen that the product prepared in Example 4 has a homogeneous structure over a large area, indicating that the two-phase material has been composited at a low size scale. Figure 6 It can be seen from the high-resolution electron microscope that the negative electrode material prepared by the present invention includes a plurality of thin layers and nanoparticles, and the thin layer structure and the nanoparticles are hybridized to obtain a composite.

[0102] (2) Battery performance test

[0103] At room temperature, within the voltage range of 0.05-3.0V, the batteries of Examples 1-8 and Comparative Examples 1-2 were subjected to charge and discharge tests at different current densities. At the same time, the specific capacity of the batteries after 300 charge and discharge cycles at a current density of 5A / g was measured. The results are shown in Table 1.

[0104] Table 1 Performance tests of embodiments and comparative examples

[0105]

[0106] As can be seen from Table 1, the rate of ball milling of different raw materials in Examples 1, 2, and 7 is significantly improved compared with the rate of ball milling of a single molybdenum oxide in Comparative Example 1. At the same time, the batteries of Examples 1, 2, and 7 have good stability after 300 cycles, thereby improving the specific capacity after the cycle. In Examples 3-6 and 8, the transition metal oxide / sulfide precursor is mixed with the transition metal oxide / sulfide and then ball milled, and then calcined. Compared with Comparative Example 2, which only uses transition metal oxide / sulfide ball milling, the battery assembled with the calcined negative electrode material has better rate performance, and Examples 3-5 still have a high specific capacity after 300 cycles.

[0107] The composite negative electrode material prepared by the present invention contains a rich heterogeneous interface layer, which realizes the coupling of crystals with different band gaps to improve the stability of the nanostructure, and enhances the kinetic process of the electrochemical reaction through the electric field construction of the heterogeneous interface. The planetary ball milling method used can simultaneously peel off the transition metal oxide and the transition metal sulfide into a thin layer structure by limiting the ball milling speed and the ball milling medium, and stack them again to avoid the re-aggregation of the same layered materials after being peeled off. It is further preferred that a precursor of a transition metal oxide or sulfide is co-ball milled with another transition metal sulfide or oxide, and the high hardness and irregular crystal structure of the precursor can be used to better transmit and increase the ball milling impact force and tangential force, thereby efficiently and fully peeling off the other transition metal sulfide or oxide.

[0108] The ball milling method used in the present invention can synthesize such materials on a large scale, which is conducive to industrial promotion. The composites prepared by traditional methods have few heterogeneous interfaces and strong randomness. The layered materials prepared by the present invention have many ordered heterogeneous interfaces, which can better improve their kinetic performance and cycle stability as negative electrode materials for sodium ion batteries. In addition, the heterogeneous structure prepared by the method of the present invention can realize more different types of transition metal compounds and sulfide combinations. The composites of traditional heterogeneous layered materials generally share one atom. Therefore, the electric field structure modulatability of the heterogeneous composite material obtained by the method of the present invention is stronger, so it is more likely to obtain a negative electrode material for a sodium ion battery with high power density and good cycle stability.

[0109] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A carbon-free negative electrode material, characterized in that: The negative electrode material is a composite of at least two thin layers of nano transition metal oxide / sulfide; or, The negative electrode material is a composite material comprising a thin layer of nano transition metal oxide / sulfide and a granular nano transition metal oxide / sulfide; The thickness of the thin layer of nano transition metal oxide / sulfide is 2-50 nm; the particle size of the granular nano transition metal oxide / sulfide is ≤80 nm.

2. The carbon-free negative electrode material according to claim 1, characterized in that: The structural formula of the nano transition metal oxide / sulfide is A x B y ; Wherein, A is selected from at least one of Mo, W, V, Ti, Co, Ni and Fe; B is selected from at least one of O and S; 0<x≤3; 0<y≤3.

3. The carbon-free negative electrode material according to claim 1, characterized in that: The nano transition metal oxygen / sulfide includes at least one of MoO3, MoO2, WO3, WO2, VO2, TiO2, CoO2, NiO2, MoS2, WS2, VS2, MnS2, TiS2, FeS2, CoS2, and NiS2.

4. A method for preparing the carbon-free negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: mixing at least two transition metal oxide / sulfide raw materials to obtain a mixed material I, and ball milling; Alternatively, the transition metal oxide / sulfide raw material is mixed with the transition metal oxide / sulfide precursor to obtain a mixed material II, which is then ball-milled and calcined.

5. The preparation method according to claim 4, characterized in that: The transition metal oxygen / sulfide raw material includes at least one of MoO3, MoO2, WO3, WO2, VO2, TiO2, CoO2, NiO2, MoS2, WS2, VS2, MnS2, TiS2, FeS2, CoS2, and NiS2; The average particle size of the transition metal oxide / sulfide raw material is 1-900 μm.

6. The preparation method according to claim 4, characterized in that: The transition metal oxide / sulfide precursor comprises a cation and an anion, wherein the cation is selected from NH4 + 、Mo 6+ 、Na + , W 6+ 、V 5+ 、Ti 4+ At least one of; the anion is selected from O 2- , S 2- At least one of; The average particle size of the transition metal oxide / sulfide precursor is 500nm-3μm.

7. The preparation method according to claim 4, characterized in that: The transition metal oxide / sulfide precursor includes at least one of ammonium molybdate, ammonium thiomolybdate, and ammonium thiotungstate.

8. The preparation method according to claim 4, characterized in that: In the mixed material I, the molar ratio of any two transition metal oxides / sulfides is m1:1; wherein 1≤m1≤8; In the mixed material II, the molar ratio of the transition metal oxide / sulfide precursor to the transition metal oxide / sulfide raw material is m2:1, wherein 1≤m2≤8.

9. The preparation method according to claim 4, characterized in that: The mass ratio of the grinding balls of the ball mill to the mixed material I is n1:1, wherein 3≤n1≤30; the mass ratio of the grinding balls of the ball mill to the mixed material II is n2:1, wherein 3≤n2≤30; The ball milling time is 5-15h, and the ball milling speed is 200-800r / min; The calcination is carried out in an inert atmosphere, which is pure N2 or Ar; the calcination temperature is 400-800°C and the calcination time is 2-10h.

10. A sodium ion battery comprising a negative electrode material, characterized in that: The negative electrode material includes the negative electrode material prepared by the preparation method according to any one of claims 4 to 9 or the negative electrode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Metal oxide-sulfide composite negative electrode material and preparation method thereof

    CN107611370A

  • Heterogeneous layered composite material for negative electrode of lithium ion battery and preparation method thereof

    CN113675391A

  • Low-cost high-performance sodium-ion battery positive electrode material as well as preparation and application thereof

    CN118231620A

  • KR20220063615A